Strategi Pengaturan Sumber Daya Manusia dalam Masa Transisi New Normal - Dessy Dwiyanti (Ideas Publishing, 2023)
Companies must have certain strategies in adapting in the new normal in order to survive. The author wants to discuss the strategy of PT. XYZ which is engaged in gas and oil mining in Sumatra to face the new normal era specifically in the field of Human Resources. This field research uses a qualitative descriptive approach with narrative analysis techniques as the data analysis technique used. PT. XYZ has a specific strategy in the field of human resources in this new normal period, including implementing a hybrid work pattern, starting to carry out offline certification pelatihan, and optimizing employee capabilities in the use of information technology systems. Companies must make plans that are flexible in facing this new normal era.